Psychological and physiological adaptation to crowd density: a study of Malaysian males - Mohd Mahudin, Nor Diana (2013)
The evidence from the literature is mixed regarding the cultural differences in human adaptation to crowds. While some studies show that members from collectivistic culture experience adverse effects of crowd density, others show that this is not the case. The extent to which culture affect human’s psychological and physiological states, therefore, remains controversial. The primary aim of this study was to investigate the reactions and adaptations of Malaysian males to short-term exposure to crowded situations. Being a collectivist culture, it is anticipated that the participants’ reactions as well as psychological and physiological adaptations to crowds would be consistent with that of collectivist cultural orientation. One Malay male participant had physiological (i.e., skin temperature, heart rate, and human thermal) responses recorded while surrounded by another 9 Malay male participants in a space 1.5m wide by 1.0m long (i.e., density approximation of 0.12m2) inside a climatic chamber, representing a jammed-pressed crowd. Subjective and behavioural measures of crowdedness and warmth sensation were recorded using questionnaires. The results show that an exposure to a high crowd density resulted in hotter body temperature than in steady state, with the chest as the warmest part, followed by thigh, calf, and upper arm. These physiological adaptations to crowdedness are further supported by participants’ psychological responses. It was also observed that the participants employed several cognitive and behavioural coping strategies to tolerate the strain induced by the crowd density. Findings are discussed in relation to the implications for the understanding of crowd behaviours among Malaysians, particularly during the Hajj season.